2007
DOI: 10.1111/j.1600-0846.2007.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms that play a role in the maintenance of the calcium gradient in the epidermis

Abstract: The typical shape of the gradient is predominantly determined by the bound calcium concentration. For both a normal and a damaged epidermis, the concentration of free calcium is mainly determined by electrophoresis in the living epidermis, whereas in the largest part of the stratum corneum diffusion is the most important factor. The convection that was determined by the transepidermal water loss did not have an effect on the calcium concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
2
8
0
3
Order By: Relevance
“…Our model shows that the gradient can only persist when the epidermal barrier locally restricts both calcium diffusion and transport in the SG and SS. Analogous results were found in mathematical continuum models investigating the calcium gradient in the epidermis4950. Thus, computational modelling highlights that TEWL alone cannot account for the calcium gradient unless coupled to the epidermal barrier.…”
Section: Discussionsupporting
confidence: 57%
“…Our model shows that the gradient can only persist when the epidermal barrier locally restricts both calcium diffusion and transport in the SG and SS. Analogous results were found in mathematical continuum models investigating the calcium gradient in the epidermis4950. Thus, computational modelling highlights that TEWL alone cannot account for the calcium gradient unless coupled to the epidermal barrier.…”
Section: Discussionsupporting
confidence: 57%
“…Several experimental (Celli et al, 2010; Jungman et al, 2012; Mauro et al, 1998; Menon et al, 1992; Tsutsumi et al, 2009) and computational approaches (Adams et al, 2012, 2015; Cornelissen et al, 2007; Denda et al, 2014) have been used to model or measure Ca 2+ fluxes in epidermis. While initial studies using fixed and sectioned tissue (Mauro et al, 1998; Menon et al, 1992) showed that after acute barrier perturbation, Ca 2+ drops in the viable layers and then recovers as the barrier recovers, a more recent study (Behne et al, 2011) reported a moderate increase in intracellular and extracellular calcium concentration as soon as 30 minutes after barrier perturbation by acetone lipid extraction in hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…This Ca 2+ gradient depends on a competent epidermal barrier (Mauro et al, 1998; Menon and Elias, 1991; Menon et al, 1994), which in turn is formed by keratinocyte Ca 2+ uptake, release, and influx (Feingold and Denda, 2012; Hu et al, 2000; Man et al, 1997). Studies from our group (Celli et al, 2010) and others (Adams et al, 2012; Cornelissen et al, 2007; Denda et al, 2012) have identified intracellular, rather than extracellular, calcium stores as the main components of the epidermal calcium gradient, and shown that ER Ca 2+ release alone can control barrier repair processes (Celli et al, 2011). …”
Section: Introductionmentioning
confidence: 97%
“…This is especially important since the rapid secretion by keratinocytes of lamellar bodies (the precursor to lipids that form the “mortar” component of the SC barrier) following barrier disruption is primarily controlled by calcium ions in the SG [ 13 ]. Whilst our conceptual model provides a feasible explanation for the formation of the calcium profile, especially as model parameters were obtained from experimental data, we cannot rule out the possibility of the contribution to this profile from other factors, such as the lipid barrier [ 78 ], electrophoresis [ 81 ], or binding of calcium to molecules such as profilaggrin [ 82 ]. In addition, if the factors that contribute substantially to the epidermal calcium profile occur on length scales of cells or smaller, our mathematical treatment of the epidermis as a porous medium may not be appropriate, and individual cell-based models (e.g.…”
Section: Discussionmentioning
confidence: 99%